Laser structuring, stress modification and Bragg grating inscription in silicon-core glass fibers - Fokine, Michael; Theodosiou, Antreas; Song, Seunghan; Hawkins, Thomas W.; Ballato, John M.; Kalli, Kyriacos; Gibson, Ursula J. (My University, 2017)
Semiconductor core fibers have numerous potential applications in optoelectronics and photonics, and the key to realizing these opportunities is controlled processing of the material. We present results on laser treatments for manipulating the core structure as well as the glass cladding. More specifically, using quasi-CW 10.6-m radiation, the clad glass can be softened and the core can be controllably melted. This is shown to permit tapering, localized formation of optical resonators, and stress modification of the as-drawn fiber and structures within it. Shown for the first time to the authors' knowledge are Bragg gratings written by modification of the silicon/glass interface using fs laser illumination at 517 nm. The cores of these fibers show stress alterations, with indications of quasi-periodic stress relief in the glass.
Keywords: Bragg gratings; Cladding (coating); Fibers; Semiconductor lasers